Adsorption of phenol on polycrystalline gold from aqueous solutions - Chamovska, Dragica; Porjazoska Kujundziski, Aleksandra (Journal of Engineering & Processing Management, 2019)
The presence of phenolic compounds as one of the most common organic pollutants in natural water (surface and ground waters) has been detected as a worldwide problem. Very small concentrations of phenols affect the quality of both environmental and household waters, and directly or indirectly impact lives in aquatic systems and humans, as well. Most of the organic compounds, containing certain functional groups, such as amino, amines, carbonyl, hydroxyl, groups containing sulfur and others, have shown ability of adsorption on metal surfaces from aqueous solutions. Cyclic voltammetry (dE/dt = 100 mV s-1) with simultaneous monitoring of the double layer (dl) capacitance (at 100 Hz and 1 mV ac signal) was used for an adsorption study of phenol on polycrystalline gold from 0.5 mol dm-3 aqueous solutions of NaHCO3. Thus, in this study an effort was made to establish a fast method, an electrochemical procedure for qualitative and quantitative determination of phenols in natural water systems.